2016
DOI: 10.1111/1365-2656.12533
|View full text |Cite
|
Sign up to set email alerts
|

Dietary niche constriction when invaders meet natives: evidence from freshwater decapods

Abstract: 201. Invasive species are a key driver of global environmental change, with frequently 21 strong negative consequences for native biodiversity and ecosystem processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 83 publications
(150 reference statements)
1
48
0
2
Order By: Relevance
“…By occupying a broad niche, theory suggests that the invader suppresses the niche size of trophically analogous native species (Jackson, Grey, et al., ; Thomson, ). Conversely, other studies have suggested that when in sympatry, the trophic niche of both the invader and native species will constrict due to dietary specialisations (Jackson, Grey, et al., ; Tran et al., 2015a, 2015b). In the experiment, there were no significant shifts in the trophic niche sizes of each species between their treatments.…”
Section: Discussionmentioning
confidence: 99%
“…By occupying a broad niche, theory suggests that the invader suppresses the niche size of trophically analogous native species (Jackson, Grey, et al., ; Thomson, ). Conversely, other studies have suggested that when in sympatry, the trophic niche of both the invader and native species will constrict due to dietary specialisations (Jackson, Grey, et al., ; Tran et al., 2015a, 2015b). In the experiment, there were no significant shifts in the trophic niche sizes of each species between their treatments.…”
Section: Discussionmentioning
confidence: 99%
“…This is of concern because crayfish invasions have generally been shown to result in strong impacts on recipient ecosystems (Lodge et al, 2012) and, given the absence of native crayfish on the African continent, these impacts are likely to be even stronger, especially upon native decapods, such as freshwater crabs from the genus Potamonautes (De Moor, 2002; Jackson et al, 2016; Nunes et al, 2016). In this study, we assess the current distribution, rate of spread and population dynamics of C. quadricarinatus populations in South Africa and Swaziland.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the release of a new species into a species-poor community that has unexploited resources would enable the invader to utilise these resources, avoiding competitive interactions with native species and enhancing their ability to integrate into the food web (Mason, Cooke, Moles & Leishman, 2008;Juncos, Milano, Macchi & Vigliano, 2015). When the introduction is into a community where resources are fully exploited and potentially limiting, theory predicts that the interactions between the introduced and native species will result in both their trophic niches becoming constricted and divergent through dietary specialisms (Bolnick et al, 2010;Tran, Jackson, Sheath, Verreycken & Britton, 2015;Jackson, Grey, Miller, Britton, & Donohue, 2016). Conversely, these increases in competitive interactions might result in the species exploiting a wider resource base and thus resulting in larger trophic niches (Svanbäck and Bolnick, 2007).…”
Section: Introductionmentioning
confidence: 99%